Traces of Mountain Rural Development Collective Policy in Local Community Relations with Migrants - Ashari Ismail (Jurnal Office, 2023)
Tracing the tracks of transitional rural development collective policies, is a study of policies designed jointly, between the village government and the local community (read: village). This development departs from local initiatives, taking into account the cultural potential and human resources. This research was carried out in Kaili Village, West Suli District, Luwu, South Sulawesi. The research was carried out using a qualitative method, a sociohistorical approach. The research targets were all community groups (indigenous and immigrant communities) in Kaili Village, and the determination of the research sample was done by purposive sampling. The results of the study show that collective rural development policies are made possible by factors: the figure of the leader, needs and security, and cultural patterns of Siri Pacce. Based on these factors there are a number of collective policies, designed within the Kaili community, namely: social solidarity/solidarity and tolerance, accommodation and assimilation, and mutual cooperation/cooperation and competition. This collective policy enables Kaili's human development, in a harmonious and associative relationship, which is in favor of the interests of the local community and immigrants. A harmonious and humane relationship between the future group and the local community is a relationship that is far from conflict. Cooperation and adjustment in social relations occur in a mutually beneficial relationship, in accordance with village rules.